The Relationship Between Engagement with Natural Beauty and Pro-environmental Behaviors Using Structural Model Analysis - Wang Hongqijie; Liu Pingping (E3S Web of Conferences)
Addressing environmental issues requires enhancing pro-environmental behaviors (PEBs). This study examines the relationship between engagement with natural beauty (ENB) and PEBs, focusing on the mediating roles of awe and connectedness to nature (CN). A total of 387 participants from 17 provinces in China completed self-report measures via an online survey platform, assessing ENB, awe, CN, and PEBs. All scales used were well-established, with internal consistencies ranging from 0.79 to 0.89. Structural equation modeling showed that ENB significantly predicts PEBs, with awe and CN as parallel mediators. Additionally, ENB predicts PEBs through a serial mediation pathway involving both awe and CN. These findings enhance the understanding of the ENB-PEB relationship, offering new theoretical perspectives and practical implications. Specifically, promoting exposure to and appreciation of natural beauty can increase ENB, encouraging more pro-environmental behaviors.